Effectiveness of Foot Care Education in Improving Knowledge among Diabetic Patients - T. Suja (Indian Journal of Nursing Sciences, 2025)
Introduction: Diabetic peripheral neuropathy is a common complication of diabetes, leading to loss of sensation in the feet and increasing the risk of foot ulcers and infections. Educating patients about proper foot care is crucial in preventing these complications. Aim: This study aimed to evaluate the effectiveness of foot care education in improving knowledge regarding diabetic peripheral neuropathy among type 2 diabetic patients. Objectives: The objectives include assessing the level of knowledge on peripheral neuropathy among diabetic patients in a selected community and determining the effectiveness of foot care education in improving diabetic patients’ knowledge regarding foot care. Methodology: A one-group pre-test–post-test research design was adopted. The study included 60 type 2 diabetic patients selected through convenience sampling from a selected Panchayat. Data were collected using pre-tested and validated tools, including a demographic variables proforma and a structured knowledge questionnaire administered through interviews. Then, foot care education was given; after 2 weeks, a post-test was conducted with the same tool. Result: Before the intervention, 36.7% of participants had poor knowledge, 45% had moderate knowledge, 15% had good knowledge, and only 3.3% had excellent knowledge. The mean pre-test score was 7.2 ± 3.4, which increased to 13.3 ± 2.8 post-intervention, yielding a mean difference of 6.1. A paired t-test revealed a statistically significant improvement in knowledge (P < 0.001). Conclusion: The study underscores the importance of incorporating foot care education into routine diabetes management programs. By enhancing patients’ knowledge about diabetic peripheral neuropathy, such educational interventions can play a pivotal role in preventing foot-related complications and improving the overall quality of life for individuals with type 2 diabetes.